Firms’ strategy formation in a fast-changing business environment : Finnish food companies adapting to Russian market changes - Koch, Anna (My University, 2021)
The purpose of this research is to understand organizations’ observing activities about the changes in their external environment. Therefore, this research is focusing on the organizational abilities to interpret fast-changing business environment and adapting their strategies accordingly. More precisely this research topic will be observed through three different sub-objectives: one to find out what scanning activities organizations use to acquire information about their external business environment, another to understand how companies conduct the interpretation process of acquired information, and lastly to expose how companies adapt their decision-making and strategy formulation to reflect changes in business environment. The initial framework for this research is selected from the existing literature since the topic of strategy formation has been widely researched. However new perspective on this topic will be provided through the empirical context. As an empirical context for this research the Finnish food industry were selected, as they have significant role in export of Finnish products to Russia. Russian turbulent business environment provides a new perspective to the research topic, due to more political effects on functioning of the market. The empirical research is collected by applying qualitative research methods with following the guidelines of theme interviews and supporting questions are structured based on the theoretical framework. Interviews will be recorded, and transcription process will be conducted afterwards. The data would be analyzed by using the operationalization table and additional information will be used to support and deepen the findings of the interviews. The empirical research findings are in line with the existing literature but also provide some new insights on this topic. The findings reveal that deviation between scanning and interpretation is relatively difficult to perform. In the interviews, on multiple occasions, these activities take place simultaneously. Whereas, in strategy formation, there is difficulties to identify whether decision-maker use relevant information before acting or whether the decision is based on the intuition of the decision-makers. Furthermore, the findings suggest that operating in fast-changing environment, such as Russian business environment, might limit organization’s ability to formulate long-term strategies.
Keywords: strategy formation, fast-changing business environment, Russia, Finnish food industry, decision making